Peta Perbandingan Kemampuan Keuangan Daerah pada Pemerintahan Kabupaten Kerinci dan Kota Sungai Penuh - Osi Hayuni Putri (Jurnal EMT KITA, 2023)
This study aims to determine a comparative map of local financial capacity of Kerinci Regency Government and Sungai Penu Municipality in Jambi, taking into account share and growth values ​​and using the quadrant method. Based on the survey results, Kerinci County is known to be located in the third quadrant and is classified as an independent prospective region. In addition, the region faces difficulties in exploring resource potential within the region as it relies on central government support. Quadrant III is characterized by PAD and DBH playing a major role in financing overall spending, but with the opportunity to experience declines due to lower growth rates. Sungai Penuh City belongs to the first quadrant classified as an independent potential region, but this quadrant is characterized by high market share and high growth value. Therefore, local governments are expected to maintain local independence in order to reduce their dependence on localities to achieve full local autonomy.